Efficient optical pumping using hyperfine levels in 145Nd3+:Y2SiO5 and its application to optical storage. (4th May 2018) - Cruzeiro, Emmanuel Zambrini; Tiranov, Alexey; Lavoie, Jonathan; Ferrier, Alban; Goldner, Philippe; Gisin, Nicolas; Afzelius, Mikael
Abstract: Efficient optical pumping is an important tool for state initialization in quantum technologies, such as optical quantum memories. In crystals doped with Kramers rare-earth ions, such as erbium and neodymium, efficient optical pumping is challenging due to the relatively short population lifetimes of the electronic Zeeman levels, of the order of 100 ms at around 4 K. In this article we show that optical pumping of the hyperfine levels in isotopically enriched 145 Nd 3 + :Y2 SiO5 crystals is more efficient, owing to the longer population relaxation times of hyperfine levels. By optically cycling the population many times through the excited state a nuclear spin flip can be forced in the ground state hyperfine manifold, in which case the population is trapped for several seconds before relaxing back to the pumped hyperfine level. To demonstrate the effectiveness of this approach in applications we perform an atomic frequency comb memory experiment with 33% storage efficiency in 145 Nd 3 + :Y2 SiO5, which is on a par with results obtained in non-Kramers ions, e.g. europium and praseodymium, where optical pumping is generally efficient due to the quenched electronic spin. Efficient optical pumping in neodymium-doped crystals is also of interest for spectral filtering in biomedical imaging, as neodymium has an absorption wavelength compatible with tissue imaging. In addition to these applications, our study is of interest for understanding spin dynamics in Kramers ions with nuclear spin.